Resolving disputes in second century BCE Herakleopolis: a study in Jewish legal reasoning in Hellenistic Egypt - Kugler, Robert A. (Journal for the study of Judaism, 2022)
Resolving Disputes challenges the consensus that the petitions to the leaders of "the πολίτευμα of the Jews in Herakleopolis" (P.Polit.Iud. 8.4-5) prove that while the Ptolemies granted Jews limited self-governance according to their ancestral traditions, the petitioners nonetheless relied almost exclusively on Ptolemaic Greek law to make their agreements and settle their arguments. Reading the appeals in their proper juridical context, this study shows how these Jewish petitioners in fact made sophisticated use of their ancestral norms, drawing from them principles that complemented and contradicted prevailing Greek law. The Jews appealing to the leaders of the πολίτευμα in Herakleopolis embraced Torah